Bibliometric Analysis of Sports Mental Toughness and Sports Self-esteem - Farok Hossen; Prasanta Kumar Das; Mukesh Mitra (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. Participate in elite sports requires a well-prepared long term training under fabourable and unfavourable environments, both physically and mentally preparation of an athlete. However, psychological aspects like sports self-esteem and mental toughness are often neglected in sports performance. The present study was conducted to find out whether the trends of two important psychological factors affect the athlete performance or not. Materials and methods. The bibliometric data was collected from the Web of Science database by searching two keywords “sports mental toughness” and “sports self-esteem.” The obtained data was then visualized through VosViewer 1.6.20. The study was conducted from 1991 to 2025. Results. The result showed that there were 2071 and 526 publications on sports self-esteem and sports mental toughness, respectively. The publications were increased with time for both the keywords, indicating growing research interest in particular topics. Conclusions. In order to enhance sports performance in relation to mental toughness and self-esteem, more research should be done nationally, to meet the gap of research study like contant specific understanding, each other influences, and understanding of coach-athletes relationship.